ANALISIS FAKTOR KLINIS DAN FAKTOR MATERNAL TERHADAP KEBERHASILAN PERSALINAN PERVAGINAM SETELAH SEKSIO SESAREA (VBAC) DI RSCS KOTA CILEGON - Mitsa, Mitsalina Durrah Judaty (Journal of Health Service Management, 2026)
Background: Vaginal Birth After Caesarean Section (VBAC) is a viable alternative to reduce the increasing rate of repeat cesarean sections. However, its success depends on several maternal and clinical factors that need to be identified to ensure maternal and neonatal safety. This study was conducted at a RSCS in Cilegon City, so the results reflect the characteristics of obstetric services at advanced health facilities. Objective: This study aims to analyze maternal and clinical factors determining the success of VBAC in a tertiary healthcare facility. Methods: This was a retrospective analytic study using medical record data of mothers with a history of cesarean section who attempted VBAC from 2023 to 2024. Independent variables included maternal age, parity, body mass index (BMI), interpregnancy interval, history of vaginal delivery, cervical dilatation at admission, and neonatal birth weight. Data were analyzed using chi-square and logistic regression tests to determine predictors of VBAC success. The research sample consisted of 100 maternal respondents, and the data was obtained from one tertiary health service facility in the period 2023–2024. Results: Out of all mothers attempting VBAC, 70% achieved successful vaginal delivery. Significant factors associated with successful VBAC were maternal age < 35 years (p < 0.05), interpregnancy interval ≥ 24 months (p < 0.01), history of previous vaginal delivery (p < 0.01), cervical dilatation ≥ 4 cm (p < 0.05), and neonatal birth weight < 3,500 g (p < 0.05). Conclusions: Maternal and clinical factors particularly maternal age, cervical readiness, and interpregnancy interval play a critical role in determining VBAC success. These findings support the need for careful antenatal selection and intrapartum monitoring to optimize VBAC outcomes.